2008
DOI: 10.1007/s11695-007-9334-5
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Weight Loss Decreases the Operative Time of Gastric Bypass at a Veterans Administration Hospital

Abstract: An 8% reduction of body weight is associated with a decrease in operative time. These preliminary data suggest that preoperative weight loss results in a technically less challenging operation in the super-obese patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 18 publications
4
43
0
6
Order By: Relevance
“…Accordingly, this was also reported in several of the included studies (11,14,18,21,22). In a meta-analysis from 2009 (25) including "the only three high-quality studies that reported this finding," a reduction in mean operating time of 23 min (95% confidence interval (CI) 13.8-32.8) was reported.…”
Section: Intraoperative Outcomessupporting
confidence: 69%
“…Accordingly, this was also reported in several of the included studies (11,14,18,21,22). In a meta-analysis from 2009 (25) including "the only three high-quality studies that reported this finding," a reduction in mean operating time of 23 min (95% confidence interval (CI) 13.8-32.8) was reported.…”
Section: Intraoperative Outcomessupporting
confidence: 69%
“…However, other retrospective studies have found that a pre-surgical weight loss of 5-10% EWL will have an impact on post-surgical morbidity (9,10,16,20), on the time duration of the surgery (19), on the amount of transfusions, and on the rate of conversions to open surgery (6,21,22). Other authors have found that pre-surgical weight loss is a predictive factor for a higher loss weight during post-surgical evolution (6,17), and would help to select those obese population who would benefit most from bariatric surgery.…”
Section: Obesity (Bmi ≥ 30 Kg/mmentioning
confidence: 96%
“…There are some observational non-controlled clinical trials (17,18) that have not demonstrated that a pre-surgical weight loss (EWL) will determine differences in post-surgical morbidity or the subsequent evolution of the patient (18,19). However, other retrospective studies have found that a pre-surgical weight loss of 5-10% EWL will have an impact on post-surgical morbidity (9,10,16,20), on the time duration of the surgery (19), on the amount of transfusions, and on the rate of conversions to open surgery (6,21,22).…”
Section: Obesity (Bmi ≥ 30 Kg/mmentioning
confidence: 99%
“…In another study, in which body composition changes were assessed by dual energy densitometry (DXA), multifrequency bioelectrical impedance analysis and air displacement plethysmography in obese patients who lost weight by following a VLCD for four months, it was found that loss of weight (an average of 20.2 kg in four months) occurred mainly at the expense of body fat and visceral mass, while muscle mass and strength were maintained [56]. In obese, elderly patients, VLCD should be used under medical supervision, especially when they have comorbidities, as these patients usually present a loss of lean mass and their vitamin and mineral requirements are often higher than young obese and middle-aged patients [55,59].…”
Section: Diet and Supplementationmentioning
confidence: 99%